Solder alloys, solder balls, solder pastes and soldered joints

CN122826072APending Publication Date: 2026-09-25SENJU METAL IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480088819.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-28
Filing Date
2024-12-25
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

另外,专利文献2中揭示Ag、Cu及Ni含量与Ge含量的平衡造成未熔合的抑制

Benefits of technology

[0024]用于解决问题的方案

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122826072A_ABST
    Figure CN122826072A_ABST
Patent Text Reader

Abstract

The present application provides a soft solder alloy, a solder paste, a solder ball, and a brazing joint, which have excellent heat cycle resistance and drop impact resistance, and excellent mountability with suppressed unmelting, wafer standing, and discoloration. The soft solder alloy has an alloy composition of Ag: 0.8 to 2.5%, Cu: 0.10 to 1.00%, Ni: 0.03 to 0.07%, Ge: 0.006 to 0.014%, Co: 0.001 to 0.030% or less, and the balance being Sn. The alloy composition preferably further contains at least one of Ga, As, Pd, Mn, In, Zn, Zr, and Mg in an amount of 0.1% or less in mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to soft solder alloys, solder balls, solder paste, and brazed joints. Background Technology

[0002] In recent years, electronic devices have been required to be highly integrated, have large capacity, and be high-speed. For example, semiconductor packaging such as BGA (Ball Grid Array) is used to achieve high integration and high functionality at the semiconductor wafer level.

[0003] Solder balls are used to form solder bumps on micro-electrodes such as BGAs. When using solder balls, for example, an adhesive flux is applied to the micro-electrode, and the solder ball is placed on the flux-coated electrode. Subsequently, the solder ball is heated in a reflow oven to melt, and the molten solder wets the micro-electrode, forming solder bumps on the micro-electrode. Therefore, when using solder balls, good wetting of the electrode is required.

[0004] Sn-Ag-Cu solder alloys have been widely used in the past as solder bump forming alloys. These alloys are highly versatile and used in various forms such as solder balls or solder paste. However, despite their versatility, there are characteristics that need further improvement depending on the application of the solder balls or solder paste. Therefore, various studies have been conducted on improving the properties of Sn-Ag-Cu solder alloys, which have been widely used in the past, to suit different applications.

[0005] Patent Document 1 discloses a solder alloy for automotive electronic components that contains Ni as a necessary element and Co and Ge as optional elements in order to improve the vibration resistance of Sn-Ag-Cu solder alloys. Patent Document 1 also discloses that during repeated bending tests to evaluate vibration resistance, cracks occur in the intermetallic compound layer or within the solder alloy region, corresponding to the alloy composition.

[0006] Therefore, Patent Document 1 discloses that, in order to suppress fracture in the intermetallic compound layer, deformation of the intermetallic compound layer can be mitigated by replacing Cu in the SnCu compound with Ni or Co, which have atomic radii smaller than Cu. It also discloses that Fe, Ni, and Co are added to suppress fracture in the solder alloy region.

[0007] Patent Document 2 discloses a solder alloy that, in order to improve shear strength and suppress incomplete fusion, contains Ni and Ge as essential elements and Co as an optional element in the Sn-Ag-Cu solder alloy. Furthermore, Patent Document 2 discloses that the balance between the Ag, Cu, and Ni contents and the Ge content suppresses incomplete fusion. Moreover, Patent Document 2 discloses that shear strength is improved through the miniaturization and solid solution strengthening of the Cu-Sn compound.

[0008] Patent Document 3 discloses a solder alloy in which, in order to suppress Ni corrosion and porosity formation, a specific relationship is defined for each constituent element in the Sn-Ag-Cu-Ni-Co-Ge solder alloy. Patent Document 3 discloses that by satisfying this specific relationship between the constituent elements, Ni diffusion is suppressed, while simultaneously facilitating the removal of pores generated within the molten solder.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 2007-237252

[0012] Patent Document 2: Japanese Patent No. 6928284

[0013] Patent Document 3: Japanese Patent No. 6700568

[0014] Patent Document 4: Japanese Patent Application Publication No. 2001-58286 Summary of the Invention

[0015] The problem the invention aims to solve

[0016] Patent Document 1 discloses Sn-Ag-Cu-Ni-Fe-Co solder alloy and Sn-Ag-Cu-Ni-Fe-Co-Ge-(P) solder alloy as the optimal solder alloys for repeated bending characteristics. Paragraphs 0036-0037 of Patent Document 1 describe how the presence of trace amounts of Fe generates a large amount of FeSn2 intermetallic compound as the nucleus for primary crystals, resulting in a refined dendritic structure and excellent results in repeated bending tests evaluating vibration resistance. Furthermore, paragraphs 0038-0039 of Patent Document 1 disclose that the SnCu intermetallic compound layer becomes thinner and grows more uniformly when containing Ni, Co, and Fe. Additionally, paragraph 0056 of Patent Document 1 discloses that Ge can be added to suppress discoloration of the solder surface.

[0017] The invention described in Patent Document 2 is an excellent invention that can suppress incomplete fusion and improve shear strength, and specifies the relationship between the contents of the constituent elements. In paragraph 0035 of Patent Document 2, the description focuses on ΔT, which represents the temperature difference between the liquidus temperature and the solidus temperature, the viscosity of the molten solder, and Ge oxide. Furthermore, paragraph 0038 of Patent Document 2 discloses that by forming a (Cu,Ni)6Sn5 compound in which a portion of Cu is replaced by Ni, the compound formed at the bonding interface becomes finer. In the same paragraph, a Sn-Ag-Cu-Ni-Ge solder alloy is described, in which Ge is dissolved in Ni, causing structural strain in the compound, thereby solid-solution strengthening of the (Cu,Ni)6Sn5 compound.

[0018] The invention described in Patent Document 3 is an excellent invention for suppressing Ni corrosion and porosity formation. In paragraph 0044 of Patent Document 3, it is disclosed that by utilizing the rapid change in melting temperature caused by Ni, the dissolution of the Ni layer can be limited to a minimum. Furthermore, in paragraph 0045 of Patent Document 3, it is disclosed that by forming a thin and brittle germanium oxide film instead of a robust tin oxide film, the porosity removal function caused by the convection of molten solder is maintained. Moreover, in paragraph 0054 of Patent Document 3, it is disclosed that in order to suppress alloy structure segregation during solidification, it is preferable to narrow ΔT.

[0019] Thus, patent documents 1-3 have explored ways to improve vibration resistance, suppress discoloration, suppress incomplete fusion, improve shear strength, and suppress Ni corrosion and porosity. However, none of the inventions described in any of these patent documents address chip lifting. Due to rapid technological innovation in recent years, there has been significant progress in the miniaturization and weight reduction of electronic components. Therefore, if different amounts of solder alloy are supplied to the two electrodes mounted on the electronic component, chip lifting may occur. Chip lifting occurs because the surface tension of the faster-melting side of the solder alloy supplied to the two electrodes pulls the chip. For example, different amounts of solder alloy can be supplied. Moreover, cases where external factors cause differences can also be cited, such as differences in the temperature rise of the solder alloy due to surrounding components, even with the same supply amount, during substrate co-mounting. Furthermore, considering the unique behavior of solder alloys, for example, the solid phase of the solder alloy immediately changes to a liquid phase after it begins to melt. However, the inventions described in Patent Documents 2 and 3 do not address the chip erection caused by these reasons.

[0020] Here, in paragraph 0032 of Patent Document 4, it is disclosed that Ni, Cu, Co, Ge, etc., can be added to the Sn-Ag solder alloy to suppress wafer stand-up. Furthermore, in the same paragraph, it is disclosed that the solder alloy containing these elements shows two endothermic peaks in differential thermal analysis. However, this only discloses the added elements; the solder alloys actually investigated are only Sn-Ag, Sn-Ag-Cu, Sn-Ag-Ni, and Sn-Ag-P. Therefore, the inclusion of Co and Ge in the solder alloys described in Patent Documents 1-3 is completely unverified.

[0021] Furthermore, when soft solder alloys are used in substrates operating in harsh environments such as automotive applications, excellent thermal cycling resistance and drop impact resistance are essential. However, the aforementioned patent documents do not address thermal cycling resistance.

[0022] Therefore, while the solder alloys described in Patent Documents 1-4 can solve various problems, it is still desirable to better reflect the actual situation during the installation of electronic components. That is, the inventions described in these documents do not explore simultaneously satisfying the characteristics disclosed in Patent Documents 1-4. Furthermore, due to the increasingly harsh operating environment caused by global warming in recent years, it is desirable to also satisfy the requirement of excellent thermal cycling resistance in solder alloys.

[0023] Therefore, the objective of this invention is to provide solder alloys, solder pastes, solder balls, and brazing joints that have excellent thermal cycling resistance and drop impact resistance, and suppress incomplete fusion, wafer stand-up, and discoloration, thus providing excellent installability.

[0024] Solution for solving the problem

[0025] The inventors have discussed the various properties of the Sn-Ag-Cu-Ni-Ge(-Co) solder alloys disclosed in Patent Documents 1 to 3. First, regarding the Sn-Ag-Cu-Ni-Ge solder alloy described in Patent Document 2, they obtained insights into how the properties vary depending on the content of each constituent element.

[0026] The insights gained indicate that while the thermal cycling resistance of solder alloys with an Ag content of 0.5% (Example 1 of Patent Document 2) is relatively poor, the thermal cycling resistance of solder alloys with a higher Ag content (Examples 2-4, 9-11, 14, 16-22 of Patent Document 2) is improved. Even these solder alloys with improved thermal cycling resistance still exhibit poor drop impact resistance, depending on their alloy composition, and may experience incomplete fusion, wafer stand-up, and discoloration.

[0027] Even the Co-containing Sn-Ag-Cu-Ni-Ge-Co solder alloy with a fine alloy structure (Example 29 of Patent Document 2) exhibits poor resistance to drop impacts, and the wafers stand up and discolor. Therefore, the formula described in Patent Document 2 is insufficient to solve the above problems, and further investigation is needed.

[0028] In Example 89 of Patent Document 1, a Sn-Ag-Cu-Ni-Ge-Co solder alloy is disclosed. However, the observation obtained is that due to the relatively low Ge content of 0.005% and the relatively high Co content of 0.040%, incomplete fusion and discoloration occur.

[0029] Example 3 of Patent Document 3 also discloses a Sn-Ag-Cu-Ni-Ge-Co solder alloy. The observation is that the alloy composition exhibits discoloration due to the relatively low Ge content of 0.005%.

[0030] Therefore, it can be seen that even Sn-Ag-Cu-Ni-Ge(-Co) solder alloys cannot achieve the necessary properties corresponding to the content of each constituent element. Here, in order to improve thermal cycling resistance and drop impact resistance, it is necessary to mitigate the stress applied to the solder alloy, thus a fine alloy microstructure is desired. To achieve a fine alloy microstructure, it is considered that as long as the liquid phase is reduced by a slight decrease in temperature from the liquidus temperature, a large amount of the liquid phase will be converted into the solid phase, thereby mutually hindering each other's growth.

[0031] As mentioned above, chip lifting occurs at different times when the solder alloy for the two electrodes is melted. It is speculated that the surface tension generated by the faster melting of the solder alloy pulls the upper end of the molten side of the chip component, thus causing the chip to lift.

[0032] More specifically, it is speculated that when the temperature of the molten solder rises from the solidus temperature to the liquidus temperature, a small increase in temperature from the solidus temperature is enough for a large amount of the solid phase to become liquid, thus increasing the influence of surface tension and causing the wafer to stand up. On the other hand, it is speculated that if even when the temperature rises from the solidus temperature, little liquid phase forms, and only a large amount of liquid phase forms near the liquidus temperature, the influence of surface tension is more suppressed, making wafer standing up less likely. Therefore, it is speculated that even if the temperature range ΔT representing the solidus temperature and the liquidus temperature is the same, this behavior varies greatly depending on the alloy composition of the solder alloy.

[0033] On the other hand, considering the heat resistance of the wafer, it is observed that in Sn-Ag-Cu-Ni-Ge-Co solder alloys, there is a tendency for a narrower temperature range of ΔT to correspond to a lower liquidus temperature. Therefore, it is speculated that a narrower temperature range of ΔT is better.

[0034] Furthermore, it is hypothesized that if a strong oxide film forms on the surface of the solder alloy, incomplete fusion will occur. On the other hand, if a suitable oxide film is formed, discoloration can be suppressed. Therefore, it is believed that moderate oxidation is necessary to suppress both incomplete fusion and discoloration.

[0035] Based on the above, it is inferred that considering the behavior from the solidus temperature to the liquidus temperature, thermal cycling resistance and drop impact resistance have opposite directions to wafer stand-up. Similarly, it is inferred that non-fusion and discoloration also have opposite directions. Conventional solder alloys have struggled to simultaneously achieve the effects required by these opposing alloy structures. Furthermore, to simultaneously satisfy excellent thermal cycling resistance and drop impact resistance, it is believed that in addition to refining the alloy structure, it is also necessary to refine the structure of the bonding interface and strengthen the Sn grains. While there has been an excessive pursuit of individual properties to achieve the necessary effects in alloy composition, it is believed that achieving a suitable level of performance is more conducive to installation.

[0036] Therefore, the inventors further investigated the content of each constituent element in detail, focusing on alloy structure and oxidation, in a manner that simultaneously achieves all the desired effects. As a result, they discovered that a narrow temperature range of ΔT is achieved only when the content of each constituent element is within a specific range, resulting in excellent thermal cycling resistance and drop impact resistance, without incomplete fusion, wafer stand-up, or discoloration. Thus, the present invention is complete.

[0037] The present invention derived from these insights is as follows.

[0038] (0) A soft solder alloy, characterized in that, by mass%, Ag: 0.8~2.5%, Cu: 0.10~1.00%, Ni: 0.03~0.07%, Ge: 0.006~0.014%, Co: 0.001~0.030%, and the balance being Sn.

[0039] (1) A soft solder alloy, characterized in that it has an alloy composition of Ag: 0.8~2.5%, Cu: 0.10~1.00%, Ni: 0.03~0.07%, Ge: 0.006~0.014%, Co: 0.001~0.030% by mass and the balance being Sn.

[0040] (2) The solder alloy as described in (0) or (1) above, wherein the alloy composition further contains at least one of Ga, As, Pd, Mn, In, Zn, Zr and Mg in an amount totaling less than 0.1% by mass.

[0041] (3) The solder alloy as described in any one of (0) to (2) above, wherein the alloy composition satisfies at least one of the following formulas (1) to (3).

[0042]

[0043] In equations (1) to (3) above, Ag, Cu, Ni, Ge and Co are the contents of the aforementioned solder alloy in terms of mass%.

[0044] (4) A solder ball, characterized in that it has a soft solder alloy as described in any one of (0) to (3) above.

[0045] (5) A solder paste, characterized in that it has a soft solder alloy as described in any one of (0) to (3) above.

[0046] (6) A brazing joint, characterized in that it has a soft solder alloy as described in any one of (0) to (3) above. Attached Figure Description

[0047] Figure 1 This shows cross-sectional SEM images of the solder alloy before and after the thermal cycling test. Figure 1 (a) is before the thermal cycling test in Example 3. Figure 1 (b) is the result of the thermal cycling test in Example 3. Figure 1 (c) is the result before the thermal cycling test of Comparative Example 16. Figure 1 (d) is the result of the thermal cycling test of Comparative Example 16.

[0048] Figure 2 These are optical microscope images of solder balls before and after being placed at high temperatures. Figure 2 (a) is before the high-temperature placement in Example 3. Figure 2 (b) is the result of high-temperature placement in Example 3. Figure 2 (c) is the result of comparison example 10 before high-temperature placement. Figure 2 (d) is the result of high-temperature placement in Comparative Example 10.

[0049] Figure 3 It is a cross-sectional SEM image showing whether there is incomplete fusion. Figure 3 (a) is Example 3. Figure 3 (b) is a comparative example 8. Detailed Implementation

[0050] This invention is explained in detail below. In this specification, the "%" related to the composition of the solder alloy is "mass %" unless otherwise specified.

[0051] 1. Soft solder alloy

[0052] (1) Ag: 0.8~2.5%

[0053] Because Ag precipitates as granular Ag3Sn, the precipitation strengthening of the solder alloy improves its thermal cycling resistance and drop impact resistance. Furthermore, by lowering the melting point, it narrows the temperature range ΔT and suppresses wafer stand-up. When the Ag content is less than 0.8%, the amount of compound precipitation is low, resulting in poor thermal cycling resistance. Moreover, if the Ag, Cu, and Ni contents are too low, the Ge content becomes relatively excessive, leading to a thick, hard, and brittle Ge oxide film, resulting in incomplete fusion. The lower limit of the Ag content is 0.8% or more, preferably 1.0% or more, and more preferably 1.2% or more.

[0054] On the other hand, if the Ag content exceeds 2.5%, the hardness of the solder alloy increases, and stress concentrates at the bonding interface, resulting in poor resistance to drop impact. The upper limit of the Ag content is 2.5% or less, preferably 2.3% or less, more preferably 2.0% or less, even more preferably 1.6% or less, and particularly preferably 1.4% or less.

[0055] In this invention, the aforementioned upper and lower limits can also be appropriately combined to define the Ag content range. The preferred range for Ag is 1.0% to 1.4%.

[0056] (2) Cu: 0.10~1.00%

[0057] Cu can suppress the rise in melting point. It can also suppress the precipitation of unfused or coarse Cu6Sn5. If the Cu content is less than 0.10%, Cu6Sn5 will not be fully precipitated, resulting in poor heat cycle resistance. The lower limit of the Cu content is 0.10% or more, preferably 0.20% or more, more preferably 0.30% or more, further preferably 0.40% or more, and particularly preferably 0.50% or more.

[0058] On the other hand, if the Cu content exceeds 1.00%, coarse Cu6Sn5 will precipitate at the bonding interface, resulting in poor resistance to drop impact. Furthermore, if the Cu content significantly exceeds 1.00%, the temperature range of ΔT will expand, and there are concerns about incomplete fusion. The upper limit of the Cu content is 1.00% or less, preferably 0.90% or less, more preferably 0.80% or less, further preferably 0.70% or less, and particularly preferably 0.60% or less.

[0059] In this invention, the aforementioned upper and lower limits can be appropriately combined to define the Cu content range. The preferred range for Cu is 0.40% to 0.60%.

[0060] (3) Ni: 0.03~0.07%

[0061] Ni inhibits the rise in melting point, suppresses incomplete fusion, promotes the refinement of Sn grains, and improves thermal cycling resistance and drop impact resistance. When the Ni content is less than 0.03%, Sn grain refinement is not possible, resulting in poor drop impact resistance. The lower limit of Ni content is 0.03% or more, preferably 0.04% or more, and more preferably 0.05% or more.

[0062] On the other hand, if the Ni content exceeds 0.07%, coarse SnNi alloy particles precipitate on the surface of the solder alloy, resulting in incomplete fusion. Furthermore, the temperature range of ΔT widens due to the increase in liquidus temperature. Consequently, with higher Ni content, drop impact resistance also deteriorates. The upper limit for Ni content is 0.07% or less, preferably 0.06% or less.

[0063] In this invention, the aforementioned upper and lower limits can be appropriately combined to define the Ni content range. The preferred range for Ni is 0.04% to 0.06%.

[0064] (4) Ge: 0.006~0.014%

[0065] Ge can suppress unfused solder and discoloration of the solder paste alloy. Without Ge, tin oxide forms on the surface of the molten solder. Tin oxide is strong and difficult to break. On the other hand, Ge added to the solder paste alloy reacts with oxygen in the atmosphere to form a hard and brittle oxide film on the surface of the molten solder. This oxide film is brittle and easily destroyed by convection within the molten solder itself or by external forces applied from the wafer during wafer mounting. Therefore, Ge inhibits the formation of an oxide film on Sn and does not maintain an oxide film on the surface of the molten solder. Instead, it promotes the fusion of the solder balls and the solder powder in the paste, contrary to the effect of Sn's oxide film.

[0066] Furthermore, since Ge reacts with oxygen in the atmosphere to form a brittle oxide film, it can suppress discoloration of the solder alloy. Moreover, because Ge does not contribute to the suppression of overcooling, the time until solidification is slowed down, resulting in finer Sn grains. Furthermore, compared to P, which is used as an oxidation suppressor, Ge provides a more sustained oxidation prevention effect. Therefore, it is particularly effective when used in solder balls, leveraging Sn's grain-refining effect and sustained oxidation suppression.

[0067] If the Ge content is less than 0.006%, discoloration will occur due to the formation of tin oxide. The lower limit for Ge content is 0.006% or more, preferably 0.007% or more, and more preferably 0.008% or more. On the other hand, if the Ge content exceeds 0.014%, a thick layer of germanium oxide will form on the surface of the solder alloy, resulting in a thick coating of hard and brittle Ge oxide film and incomplete fusion. Incomplete fusion will also occur when the combined amount of Ag, Cu, and Ni is relatively low. The upper limit for Ge content is 0.014% or less, preferably 0.012% or less, more preferably 0.011% or less, further preferably 0.010% or less, and particularly preferably 0.009% or less.

[0068] In this invention, the aforementioned upper and lower limits can be appropriately combined to define the content range of Ge. The preferred range for Ge is 0.006~0.012%.

[0069] (5) Co: 0.001~0.030% or less

[0070] In the solder alloy of this invention, Co suppresses the rise in melting point and, through a synergistic effect with Ni, inhibits incomplete fusion, promotes the refinement of Sn grains, and improves thermal cycling resistance and drop impact resistance. Although the Co content in the solder alloy of this invention is less than that of Ag or Cu, the absence of Co would result in poor drop impact resistance, incomplete fusion, and wafer stand-up. Therefore, although Co is a trace additive element, it is treated as an essential element in this invention.

[0071] When the Co content is less than 0.001%, it impairs the refinement of Sn grains and results in poor thermal cycling resistance. The lower limit of the Co content is 0.001% or more, preferably 0.004% or more, more preferably 0.006% or more, even more preferably 0.0070% or more, and particularly preferably 0.008% or more. On the other hand, if the Co content exceeds 0.030%, coarse SnCo compounds are formed on the surface of the solder alloy, resulting in the simultaneous presence of solid and liquid phases in the molten solder. This causes the liquidus temperature to rise, and the wettability to be poor, leading to incomplete fusion. The upper limit of the Co content is 0.030% or less, preferably 0.020% or less, more preferably 0.015% or less, even more preferably 0.012% or less, and particularly preferably 0.010% or less.

[0072] In this invention, the aforementioned upper and lower limits can be appropriately combined to define the content range of Co. The preferred range for Co is 0.006~0.012%.

[0073] (6) Balance: Sn

[0074] The balance of the solder alloy of the present invention is Sn. In addition to the aforementioned elements, unavoidable impurities may also be present. The balance of the solder alloy of the present invention may also be Sn and unavoidable impurities. The presence of unavoidable impurities does not affect the aforementioned effects. Furthermore, since P acts as a solidification nucleus for Sn grains to suppress supercooling, the time until solidification is prolonged, causing the Sn grains to become excessively large; therefore, it is preferable to exclude P. Additionally, in the present invention, there is a concern about the formation of SnFe intermetallic compounds. This increases the processing difficulty; therefore, it is preferable to exclude Fe.

[0075] (7) At least one of Ga, As, Pd, Mn, In, Zn, Zr and Mg, in total of less than 0.1%.

[0076] The solder alloy of the present invention, without impairing the effects of the present invention, may contain at least one of Ga, As, Pd, Mn, In, Zn, Zr, and Mg in a total amount of less than 0.1%. Preferably, the total amount is less than 0.08%. The lower limit of the content is not particularly limited, but it is acceptable as long as it is 0.001% or more.

[0077] (8)(1)~(3)

[0078]

[0079] In equations (1) to (3) above, Ag, Cu, Ni, Ge and Co are the contents of the aforementioned solder alloy in terms of mass%.

[0080] The solder alloy of the present invention can further fully realize all its effects by satisfying equations (1) to (3). Preferably, at least one of equations (1) to (3) is satisfied, and most preferably all of equations (1) to (3) are satisfied. Regarding equation (1), Ag is an element that helps the wafer stand-up, and Cu, Ni, Ge and Co are elements that help with effects other than wafer stand-up. Regarding thermal cycling resistance, drop impact resistance and wafer stand-up, the behavior is opposite from the liquidus temperature to the solidus temperature, but it is preferable that not only one effect is prominent enough, but that an overall balance is achieved.

[0081] Therefore, it is required to control the behavior of the liquid and solid phases within the temperature range from the liquidus temperature to the solidus temperature. In order to meet the requirements given this reality, the solder alloy of the present invention preferably satisfies equation (1).

[0082] Furthermore, by satisfying equation (2), the solder alloy of the present invention can enhance the synergistic effect of Ni and Co to a more sufficient level, and can fully utilize the miniaturization effect of Sn grains. In addition, it can make ΔT narrower, suppress incomplete fusion, and achieve other effects.

[0083] The solder alloy of the present invention achieves an excellent balance of constituent elements that form compounds with Sn by satisfying equation (3). Therefore, AgSn, CuSn, NiSn, and SnCo compounds do not bulge out excessively during solidification. As a result, the solder alloy satisfying equation (3) exhibits high performance and excellent thermal cycling resistance.

[0084] The lower limit of formula (1) is preferably 400,000 or more, more preferably 428,571 or more, even more preferably 500,000 or more, even more preferably 535,714 or more, particularly preferably 600,000 or more, most preferably 625,000 or more, and may be 714,286 or more or 750,000 or more. The upper limit of formula (1) is preferably 1,458,334 or less, more preferably 1,437,500 or less, even more preferably 1,250,000 or less, even more preferably 1,000,000 or less, particularly preferably 937,500 or less, and most preferably 875,000 or less.

[0085] In this invention, the aforementioned lower and upper limits can be appropriately combined as the range of equation (1). The preferred range of equation (1) is 600000~937500.

[0086] The lower limit of formula (2) is preferably 2.50 or more, more preferably 3.75 or more, even more preferably 5.00 or more, and even more preferably 6.25 or more. The upper limit of formula (2) is preferably 8.40 or less, more preferably 8.33 or less, and even more preferably 7.50 or less.

[0087] In this invention, the aforementioned lower and upper limits can be appropriately combined to form the range of equation (2). The preferred range of equation (2) is 5.00 to 7.50.

[0088] The lower limit of formula (3) is preferably 0.000168 or more, more preferably 0.000180 or more, more preferably 0.000192 or more, even more preferably 0.000200 or more, and particularly preferably 0.000240 or more. The upper limit of formula (3) is preferably 0.004900 or less, more preferably 0.000900 or less, even more preferably 0.000800 or less, even more preferably 0.000480 or less, particularly preferably 0.000460 or less, and most preferably 0.000400 or less. It can be 0.000336 or less, 0.000300 or less, 0.000280 or less, or 0.000252 or less.

[0089] In this invention, the aforementioned lower and upper limits can be appropriately combined as the range of equation (3). The preferred range of equation (3) is 0.000200~0.000400.

[0090] These formulas are obtained through the interdependence of the constituent elements. The reason is that an alloy is a combination of all the constituent elements, and each constituent element affects the others. Thus, in addition to adjusting the optimal content of each constituent element, the solder alloy of the present invention, which satisfies formulas (1) to (3), is set within a range that fully takes into account the interdependence of each constituent element. Therefore, if each constituent element is within the above range and satisfies formulas (1) to (3), various characteristics that were previously difficult to achieve can be simultaneously achieved at a high level in a single composition.

[0091] In the calculations of equations (1) to (3), the values ​​shown in Tables 1 and 2, which are based on the measured values ​​of the alloy composition, are used. Regarding the values ​​calculated by equations (1) to (3), equation (1) is calculated as an integer, equation (2) is calculated to the second decimal place, and equation (3) is calculated to the sixth decimal place. Since this calculation rule is used in this application and all solder alloys must be treated in the same way, it is also used in other calculations related to solder alloys described in other documents.

[0092] Furthermore, in the embodiments described later, when the determination result is "◎", it indicates a comparison with "○", which is particularly preferred in practice. Since "○" is a more preferred result than before, it is treated as an embodiment within the scope of the present invention. Since "×" or "△" is an insufficient result in the present invention, it is outside the scope of the present invention and is treated as a comparative example.

[0093] 2. Solder ball

[0094] The solder alloy of the present invention can be used as solder balls. The solder balls of the present invention are used to form bumps on electrodes and substrates of semiconductor packages such as BGAs. The diameter of the solder balls of the present invention is preferably in the range of 1 to 1000 μm. The solder balls can be manufactured using conventional solder ball manufacturing methods.

[0095] 3. Solder paste

[0096] The solder paste of the present invention is a mixture of solder powder composed of the above-mentioned alloy composition and flux. The flux used in the present invention is not particularly limited as long as it can be soldered by common methods. Therefore, any commonly used flux appropriately mixed with rosin, organic acid, activator, thixotropic agent, and solvent is acceptable. In the present invention, the mixing ratio of metal powder component to flux component is not particularly limited, but preferably it is: metal powder component: 70-90% by mass, flux component: 10-30% by mass.

[0097] 4. Brazed joints

[0098] The brazing joint of the present invention is preferably used for joining at least two or more components. The term "components to be joined" is not particularly limited as long as they are electrically connected using the soft solder alloy of the present invention, such as components, substrates, electronic parts, printed circuit boards, insulating substrates, heat sinks, lead frames, semiconductors and power modules using electrode terminals, inverter products, etc.

[0099] 5. Manufacturing method of soft solder alloy

[0100] The solder alloy of the present invention is preferably manufactured by adding Sn-Ni master alloy, Sn-Co master alloy, and Sn-Ge master alloy to an alloy containing specific amounts of Ag and Cu in Sn, such that the content of each constituent element is in a specific amount. Because Ni and Co have high melting points, if added to Sn alone, they will leave insoluble residues, resulting in coarse SnNi or SnCo alloys. Furthermore, because Ge has a high melting point, it will also leave insoluble residues and is generally not suitable for addition alone. Therefore, regarding Ni, Co, and Ge, it is preferable to add them to the SnAgCu alloy in the form of master alloys with Sn.

[0101] 6. Other

[0102] The solder alloy of the present invention can be manufactured as a low-alpha-ray alloy by using low-alpha-ray materials as its raw materials. This low-alpha-ray alloy, when used in the formation of solder bumps around a memory chip, can suppress soft errors.

[0103] Example

[0104] The present invention is illustrated by the following embodiments, but the present invention is not limited to the following embodiments.

[0105] To verify the effectiveness of the present invention, the soft solder alloys listed in Table 1 were used to measure (1) ΔT, and to conduct (2) heat resistance cycling test (TCT) and (3) drop impact test (DROP) to confirm whether there was (4) lack of fusion, (5) wafer standing up and (6) discoloration.

[0106] (1)ΔT

[0107] For the solder alloys shown in Tables 1 and 2, the temperatures were determined from the DSC curves. The DSC curves were obtained using a SEIKO Instruments DSC (model: 6200) at an atmospheric temperature with a heating rate of 5°C / min. The liquidus temperature was determined from the obtained DSC curves. Furthermore, the solidus temperature was also evaluated based on the DSC curves. The value obtained by subtracting the solidus temperature from the liquidus temperature was defined as ΔT. A value less than 11°C was marked with "◎". A value between 11°C and 40°C was marked with "○". A value exceeding 40°C was marked with "△".

[0108] (2) Thermal Cycling Test (TCT)

[0109] The solder alloys shown in Tables 1 and 2 were atomized to form solder powder. This powder was then mixed with a soldering flux (GLV, manufactured by Senju Metal Industries, Ltd.) composed of rosin, solvent, activator, thixotropic agent, and organic acid to prepare solder pastes for each solder alloy. The solder paste consisted of 88% alloy powder and 12% flux by mass. The solder paste was printed onto a 0.8mm thick printed circuit board (material: FR-4) using a 100μm thick metal mask. Fifteen BGA components were then mounted using a pick-and-place machine, and reflow soldering was performed at a maximum temperature of 245°C for 60 seconds to create a test substrate.

[0110] The fabricated test substrate is placed in a thermal cycling test apparatus set to a low temperature of -40°C, a high temperature of +125°C, and a holding time of 10 minutes. The number of cycles is calculated from the initial resistance value of 3~5Ω to the point where the resistance value of at least one BGA component exceeds 15Ω. A cycle count of 700 or more is marked with "◎". A cycle count of 650~699 is marked with "○". A cycle count of less than 650 is marked with "×".

[0111] (3) Drop Impact Test

[0112] The solder paste was prepared in the same manner as in (2). The solder paste was printed onto a 0.8 mm thick printed circuit board (material: FR-4) using a 100 μm thick metal mask. Five BGA components were then mounted on each board using a pick-and-place machine. Reflow soldering was performed at a maximum temperature of 240 °C for 60 seconds to create two test boards. Subsequently, the BGA components were individually assembled.

[0113] Next, the test substrate was bolted to the base with the BGA components facing the base. The resistance value was measured according to JEDEC standards in this configuration, and an impact of 1500G was applied to evaluate impact resistance. The number of drops up to 50% increase in resistance was used to evaluate the cracking progress. A result of 100 or more drops was marked with "◎". A result of 90 or more drops but less than 100 drops was marked with "○". A result of less than 90 drops was marked with "×".

[0114] (4) Not fused

[0115] For the solder alloys shown in Tables 1 and 2, the presence or absence of unfused components was verified. The verification method involved casting, rolling, or stamping the solder alloys blended according to the compositions of each embodiment and comparative example to produce small sheet-like components (2mm (length) × 2mm (width) × 0.1mm (thickness)). These small sheets were then shaped into plates of a specific size and placed on Cu plates treated with OSP (Organic Solderability Presevation) flux. After reflow soldering, the surfaces were cleaned and placed in an environment of 125°C and 100% RH for 24 hours.

[0116] Furthermore, solder balls (300 μm in diameter in this example) made using a solder alloy with Ag of 3.0%, Cu of 0.5%, and the balance Sn (Sn-3.0Ag-0.5Cu) were placed in an environment of 125°C and 100% RH for 24 hours, similar to the small component. Next, flux was applied to a sample made of the solder alloy of the example or comparative example, and a specific number of solder balls were placed on it. In this example, there were 9 solder balls, prepared in 5 pieces. Then, after reflowing in the atmosphere at a maximum temperature of 240°C for 60 seconds, the number of solder balls that did not fuse was counted. "Not fused" refers to a state where the small component and the solder ball are not bonded. A case where no one failed to fuse was marked with "◎". A case where one failed to fuse was marked with "×".

[0117] (5) Chip stand up

[0118] The solder paste was prepared in the same manner as in (2). The solder paste was printed onto the Cu pads of a 6-layer printed circuit board (FR-4, Cu-OSP) using a 150μm metal mask, and then 12 3216 chip resistors were mounted using a pick-and-place machine. Subsequently, the substrate was melted and reflowed under heating conditions of a maximum temperature of 245°C and a holding time of 40 seconds to create a test substrate. The number of chips that stood upright after mounting was counted. A count of 0 chips was marked with "◎". A count of 1 chip was marked with "○". A count of 2 or more chips was marked with "×".

[0119] (6) Color change

[0120] The solder alloys shown in Tables 1 and 2 were placed in a crucible and heated to 245°C for 10 minutes to melt them. Molten solder was dripped from an orifice at the bottom of the crucible, and the resulting droplets were rapidly cooled to room temperature (18°C) to form solder balls with a diameter of 600 μm. The solder balls were then heated in an atmospheric environment at 300°C for 300 seconds, and the brightness change was measured. Brightness was measured using a KONICA MINOLTA CM-3500d spectrophotometer with a D65 light source and a 10-degree field of view, according to JISZ 8722 "Methods for Determination of Color - Color of Reflected and Transmitted Objects". The spectral transmittance was determined by the color value (L). ,a ,b Find it. Also, (L) ,a ,b (This is based on JIS Z 8729 "Methods of Representation of Colors - L") a b Color scheme and L u v The color scheme is specified in the "color system". For brightness, a For redness, b The color is yellow. A brightness of 70 or higher is marked with "◎". A brightness below 70 is marked with "×".

[0121] The results of the above evaluations are shown in Tables 1 and 2.

[0122] [Table 1]

[0123]

[0124] [Table 2]

[0125]

[0126] As shown in Table 1, Examples 1 to 30 were evaluated as practically durable because the content of each constituent element was appropriate. Moreover, Examples 2 to 5, 8, 9, 11, 12, 15 to 20 and 22 to 30, which satisfy equations (1) to (3), showed extremely excellent results in all evaluations.

[0127] On the other hand, as shown in Table 2, Comparative Example 1 had a lower Ag content, resulting in poor TCT. Comparative Example 2 had a higher Ag content, resulting in poor DROP.

[0128] Comparative Example 3 had a lower Cu content, resulting in a poorer TCT result. Comparative Example 4 had a higher Cu content, resulting in a poorer DROP result.

[0129] Comparative Examples 5 and 6 had poor DROP due to their low Ni content. Comparative Example 7 had poor fusion due to its high Ni content, resulting in a wider ΔT range. Comparative Example 8 had even higher Ni content, resulting in poor TCT and DROP, and a wider ΔT range.

[0130] Comparative Examples 9-11 showed discoloration due to their low Ge content. Comparative Examples 12 and 13 showed incomplete fusion due to their higher Ge content.

[0131] Comparative Example 14 had a poor TCT due to its low Co content. Comparative Example 15 had a high Co content, resulting in incomplete fusion and a wider ΔT range due to the high Co content, leading to incomplete fusion and discoloration.

[0132] Comparative Example 16, lacking Co and with low Ag and Ni content, exhibited poor TCT and incomplete fusion. Comparative Example 17, with its low Ge content, resulted in discoloration. Comparative Examples 18-24, with their low Ge and high Ag content, exhibited poor DROP and discoloration.

[0133] Figure 1 This shows cross-sectional SEM images of the solder alloy before and after the thermal cycling test. Figure 1 (a) is before the thermal cycling test in Example 3. Figure 1 (b) is the result of the thermal cycling test in Example 3. Figure 1 (c) is the result before the thermal cycling test of Comparative Example 16. Figure 1 (d) is the result after the thermal cycling test of Comparative Example 16. Figure 1 (a) and Figure 1 As shown in (b), in Example 3, after the thermal cycling test, although Sn and the Ag3Sn surrounding Sn became slightly coarser, the coarsening was suppressed to a degree that did not degrade the properties. On the other hand, as Figure 1 (c) and Figure 1 As shown in (d), after the thermal cycling test of Comparative Example 16, Sn, Ag3Sn and (Cu,Ni)6Sn5 became significantly coarser.

[0134] Figure 2 These are optical microscope images of solder balls before and after being placed at high temperatures. Figure 2 (a) is before the high-temperature placement in Example 3. Figure 2 (b) is the result of high-temperature placement in Example 3. Figure 2 (c) is the result of comparison example 10 before high-temperature placement. Figure 2 (d) is the result of comparative example 10 after being placed at high temperature. Figure 2 (a) and Figure 2 As shown in (b), no solder ball oxidation was observed in Example 3 after placement at high temperature. On the other hand, as Figure 2 (c) and Figure 2As shown in (d), Comparative Example 10 turned black after being placed at high temperature.

[0135] Figure 3 It is a cross-sectional SEM image showing whether there is incomplete fusion. Figure 3 (a) is Example 3. Figure 3 (b) is a comparative example 8. For example... Figure 3 As shown in (a), in Example 3, it is fused with the solder ball. On the other hand, as Figure 3 As shown in (b), Comparative Example 8 showed no fusion.

Claims

1. A soft solder alloy, characterized in that, It has an alloy composition of Ag: 0.8~2.5%, Cu: 0.10~1.00%, Ni: 0.03~0.07%, Ge: 0.006~0.014%, Co: 0.001~0.030% by mass, with the balance being Sn.

2. The solder alloy according to claim 1, wherein, The alloy composition further contains at least one of Ga, As, Pd, Mn, In, Zn, Zr and Mg in an amount totaling less than 0.1% by mass.

3. The solder alloy according to claim 1 or 2, wherein, The alloy composition satisfies at least one of the following equations (1) to (3): In equations (1) to (3) above, Ag, Cu, Ni, Ge and Co are the contents of the solder alloy by mass%.

4. A solder ball, characterized in that, It has the solder alloy as described in claim 1 or 2.

5. A solder paste, characterized in that, It has the solder alloy as described in claim 1 or 2.

6. A brazed joint, characterized in that, It has the solder alloy as described in claim 1 or 2.

Citation Information

Patent Citations

  • Solder paste for joining chip part

    JP2001058286A

  • Lead-free solder alloy for electronic member to be mounted on automobile, solder ball and electronic member

    JP2007237252A